Frugal Innovation for Point-of-Care Diagnostics Controlling Outbreaks and Epidemics - Miesler, Tobias; Wimschneider, Christine; Brem, Alexander; Meinel, Lorenz (ACS Biomaterials Science and Engineering, 2020)
Today epidemics of infectious diseases occur more often and spread both faster and further due to globalization and changes in our lifestyle. One way to meet these biological threats are so-called "Frugal Innovations", which focus on the development of affordable, rapid, and easy-to-use diagnostics with widespread use. In this context, point-of-care-tests (POCTs), performed at the patient's bedside, reduce extensive waiting times and unnecessary treatments and enable effective containment measures. This Perspective covers advances in POCT diagnostics on the basis of frugal innovation characteristics that will enable a faster, less expensive, and more convenient reaction to upcoming epidemics. Established POCT systems on the health care market, as well as currently evolving technological advancements in that sector are discussed. Progress in POCT technology and insights on how to most effectively use them allows the handling of more patients in a shorter time frame and consequently improves clinical outcomes at lower cost.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Emerging Markets; Epidemics; Frugal Innovation; Point-of-Care-Tests